2023
DOI: 10.3390/w15173047
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Antibiotics Alter Microbial Communities and Induce High Abundances of Antibiotic-Resistant Genes in Ornamental Water

Lingyun Tian,
Hao Fang,
Qianbo Mao
et al.

Abstract: Antibiotic resistance poses a significant threat to the public health domain. A favorable platform for generating and disseminating antibiotic-resistant genes (ARGs) and antibiotic-resistant bacteria (ARB) is provided by landscaped fish ponds created by urbanization. This research delved into the effects exerted by different concentrations of specific antibiotics, namely tetracycline and ciprofloxacin, on the microbial community composition present in water samples obtained from a landscape pond. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The antibiotic use in the ornamental fish industry has led to the selection of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the ornamental fish trade globally [ 7 , 8 ]. For instance, our previous study revealed that Aeromonas and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibiotic use in the ornamental fish industry has led to the selection of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the ornamental fish trade globally [ 7 , 8 ]. For instance, our previous study revealed that Aeromonas and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…isolated from carriage water samples demonstrated resistance to over 15 types of antibiotics, and most of them carried multiple ARGs, such as qnrS2 , intl1 , tetD , and tetE [ 6 ]. Moreover, it has been documented that antibiotics administered at subtherapeutic levels can induce the development of an environmental resistome [ 8 , 10 ]. For example, enrofloxacin at concentrations above 0.064 ng L −1 can result in the selection of ARB [ 11 ].…”
Section: Introductionmentioning
confidence: 99%